The use of magnetic nanoparticles for immobilization and recycling of enzymes. (13th August 2018) - Furtado, Shirley; Brandes, Mariana; Alamón, Catalina; Botasini, Santiago; Cantera, Ana M.B.
ABSTRACT: The use of nanostructured materials for enzyme immobilization is an active field of research due to its large surface area and the new emergent properties derived from its size. The present work is focused on the synthesis of magnetic nanoparticles for the adsorption of cysteine-proteolytic enzymes extracted from Bromelia antiacantha Bertol (Bromeliaceae) fruit. The results show that enzyme adsorption is highly dependent on the temperature and pH. The biocatalyst activity increased up to 40 %, once immobilized onto the magnetic nanoparticles. In addition, they can be recovered using a magnet allowing them to be reused up to 5 cycles with a marginal loss (5 %) of the initial activity.